Counseling On Making Facial Scrub Gel From Coffee Grounds (Coffee Arabica Linn): Penyuluhan Pembuatan Gel Scrub Wajah Dari Ampas Kopi (Coffee Arabika Linn) - Apriani, Aida; Muna, Tajul; Angraini, Widya (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Gel scrub is a skin care product containing scrub granules to remove dead skin cells and dirt. Gel scrub is made using a gelling agent, namely carbopol. The community service activity was implemented using lectures, demonstrations, and a question-and-answer session. The purpose of this outreach is to enable the community to process coffee grounds, which are usually useless waste, into a pharmaceutical preparation, namely gel scrub, which has high economic value, thereby improving the community's economy (entrepreneurship). The outcome of this community service is to increase community knowledge and enable the community to process coffee waste into a gel scrub with economic value, thus improving the local economy. Based on survey results, the level of community knowledge regarding gel scrub education during the pretest was 15%, while after the posttest it was 80%.